Discourse Analysis of The Film Entitled “Dirty Vote” Using Van Dijk’s Model - M. Fathoni; Zahratul Fikni; Ayu Surayya; Muhamad Husnu (Departement of Mathematics Education, 2024)
This research is discourse analysis research on the film directed by Dandhy Dwi Laksono entitled